PENINGKATAN KECAKAPAN HIDUP MELALUI PEMBELAJARAN TEMATIK POKOK BAHASAN PEMANASAN GLOBAL SISWA SEKOLAH DASAR - Rede, Amram (Bioedukasi Jurnal Pendidikan Biologi, 2010)
Development of Thematic Learning of Global Warming Influence for Life skills of Elementary School Student. Thematic learning is application of holistic education to see a problem from different perspectives. Global warming is a complex problem, it must be expected in holistic conduct. Thematic learning is the right choice to teaching global warming for elementary school students. The research was divided into two stages. Research development stages and experiment research stages. Development of research was aimed at developed main theme of global warming into several theme. Furthermore each theme corresponding to subject-metter. EachÂ  subject-matter will be developed by adoptedÂ  Jerol-Kemp development. Research experiments aimed to verify influence of thematic learning toward life skills in addressing problem of global warming. Data were collected using a rubric. Test of hypothesis using anova. A number of 118 fifth grade of the students netted as a sample. The results showed highly significant thematic learning toward life skills with value r = 0.01 of error probability is smaller than standard error a = 0.05. Anova results is indicated that LSD value is 72 more than 41 in conventional learning.Kata kunci: pembelajaran tematik, kecakapan hidup, pemanasan global.